L’Irrésistible Ascension d’Arturo Ui, une pièce « d’histoire immédiate » ? - Emmanuelle Hénin (Sillages Critiques)
The Resistible Rise of Arturo Ui, written by Brecht in 1941, expresses in an exemplary way the relationship to immediate history, since it denounces the nazi regime in place, and the relationship to historical sources (biographies, photos) and literary sources – among which Richard III, which was itself written a century after the events it stages. Brecht’s play offers a perfect example of a play about the immediate past, represented in a refective way.